2007
DOI: 10.1080/20786204.2007.10873508
|View full text |Cite
|
Sign up to set email alerts
|

Profile of the geriatric patient hospitalised at Universitas Hospital, South Africa

Abstract: BackgroundThe elderly population in Africa is unevenly distributed across the continent, with the highest percentage of elderly living in the Southern African region. In 1996, the elderly population of South Africa (65 years and older) was roughly 6.7%, and was calculated to be 10.4% by 2025. If the latter expectation is anywhere near realistic, it stands to reason that the Department of Health should make timely provision for the care of these future patients, as the prevailing disease patterns within a popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…In South Africa, the elderly population has increased from 6.7% in 1996 to 9% (i.e. 5.3 million) of the population in 2019 [ 4 , 14 ] and it has been estimated to rise to 10.4% by 2025 [ 15 ]. It is therefore of necessity that all healthcare facilities across the country make provision for the care of these group of patients, since it has been shown that the prevailing disease patterns within these age group vary from that of the younger generation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, the elderly population has increased from 6.7% in 1996 to 9% (i.e. 5.3 million) of the population in 2019 [ 4 , 14 ] and it has been estimated to rise to 10.4% by 2025 [ 15 ]. It is therefore of necessity that all healthcare facilities across the country make provision for the care of these group of patients, since it has been shown that the prevailing disease patterns within these age group vary from that of the younger generation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, geriatric patients are four to six times more likely to be admitted to an emergency unit than a non-elderly patient [ 16 ]. There is an urgent need for healthcare facilities to profile the elderly patients presenting at their emergency department (ED) in order for adequate training to be implemented and for appropriate strategies and instruments to be put in place [ 14 ]. Management of geriatric patients in the ED is a vital issue, not only because of their rapidly increasing population, but also because of their specific and complex characteristics and risk of adverse outcomes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in the total study group of 791 patients hospitalised in the Geriatric Unit was 16.6% (n = 131), 6 and in the anaemic group it was 18.0% (27/150) for female and 18.6% (16/86) for male patients, confirming that anaemia is associated with a slightly increased mortality rate in geriatric hospitalised patients. 2…”
Section: Resultsmentioning
confidence: 65%
“…Other countries have reported a different disease spectrum in a similar population. In one of the few African studies, hypertension, heart failure, ischemic heart disease, and anemia were reported as the most predominant causes of hospitalization [ 15 ]. Besides diabetes, the main cause for hospitalization in Europe, the other main conditions include cardiovascular diseases and pulmonary diseases, which are similar to what we observed in this study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%